1989
DOI: 10.1063/1.456820
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational assignments and intensity considerations of the fluorescence excitation spectra of jet-cooled S1 t r a n s-stilbene and its three isotopic analogues

Abstract: Vibrational mode assignments of S1 trans-stilbene (tSB) in a jet, particularly those for fundamental vibrational levels above the isomerization barrier, are reported with three partially isotope-substituted analogues (C6 H5 –13CH=13CH–C6 H5 , C6 H5 –CD=CD–C6 H5 , and C6 D5 –CH=CH–C6 D5 ). Vibrational levels are assigned on the basis of the frequency shifts due to isotopic substitution. The established mode assignments then enable us to discuss the individual band intensities in the fluorescence excitation spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…This inversion, already explained for transstilbene by Negri et al 4b but somehow passed unnoticed, is not against observed isotopic wavenumber shifts. 5,6 As the elements of the Duschinsky matrix show, the 7 , 8 and 9 modes of S 1 cis-stilbenes are still expressible in terms of the same group of S 0 modes, although the internal oscillators contributing most are no longer the same. This is well seen also in the low-wavenumber region where the 36 and 37 modes in the S 1 state are different sign combinations of the corresponding modes in the S 0 state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inversion, already explained for transstilbene by Negri et al 4b but somehow passed unnoticed, is not against observed isotopic wavenumber shifts. 5,6 As the elements of the Duschinsky matrix show, the 7 , 8 and 9 modes of S 1 cis-stilbenes are still expressible in terms of the same group of S 0 modes, although the internal oscillators contributing most are no longer the same. This is well seen also in the low-wavenumber region where the 36 and 37 modes in the S 1 state are different sign combinations of the corresponding modes in the S 0 state.…”
Section: Resultsmentioning
confidence: 99%
“…A series of experimental studies reporting vibronic transitions for a number of transstilbene isotopomers were published some time ago, 5,6 while for the S 1 cis-stilbene, owing to its short lifetime and difficulties in accessing the required pump and probe wavelengths, a picosecond time-resolved resonance Raman study appeared only recently. 7 for reabsorption and detection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The latter have been resolved until now only in jet-cooled gaseous 1PV under collision-free conditions. [47][48][49][50]56 In condensed matter, the fluctuations of the dielectric polarizability of the molecular environment cause inhomogeneous broadening of the vibronic transition energies, especially in amorphous matrices, where the apparent fluorescence excitation spectrum of 2PV shifts with the frequency of detection by ⌬Ϸ400 cm Ϫ1 , see Fig. 3.…”
Section: A Fluorescence and Absorption Spectramentioning
confidence: 99%
“…Fluorescence and absorption spectra of 1PV at T ϭ4 K were recorded in solid solution 55 and under collisionfree conditions. [47][48][49][50]56 Site-selective fluorescence spectra at low temperatures were measured for nPVs (nϭ2 -4) and PPV, 43,57 but a vibronic analysis of the spectra including progressions and combination bands was not carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Its S 0 and S 1 potential energy surfaces, with special emphasis to the potential energy curves along the torsion around the ethylenic CyC bond, have been studied by many authors and by different theoretical approaches [1 -12]. Spectroscopically, several IR, Raman and UV studies in solution, solid matrices and supersonic beams have been performed on the vibrational frequencies to gain information on the mechanism and the dynamics of the photoisomerization process [7,9,10,[13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%